MP04: Interim analysis of the impact of the Emergency Department Transformation System on ambulance offload delay. (15th May 2017) - Pawa, S.; Van Aarsen, K.; Dukelow, A.; Lizotte, D.; Zheng, M.
Abstract : Introduction: Emergency Department Systems Transformation (EDST) is a bundle of Toyota Production System based interventions implemented in two London, Canada tertiary care Emergency Departments (ED) between April 2014 and July 2016 to improve patient care by increasing value and reducing waste. Some of the 17 primary interventions included computerized physician order entry optimization, staff schedule realignment, physician scorecards, and a novel initial assessment process. Offload delays are associated with longer hospital length of stay and delayed admission, and may increase morbidity and mortality. Delays also result in fewer circulating ambulances in the community. CIHI sets a benchmark of 30 minutes as an acceptable offload target. It is possible that EDST may have impacted offload times.Methods: Middlesex-London EMS provided offload times. Data was collected from London Health Sciences Centre including daily ED visit volumes, ED occupancy, offload nursing hours, and site variation. A binomial logistic regression analysis was performed to determine the impact of interventions and confounding variables on the proportion of patients meeting CIHI benchmark. A chi-square analysis was done comparing proportion of patients meeting the benchmark in the first 3 months versus the last 3 months to identify overall impact of EDST to date.Results: Increased offload nursing hours had a positive impact (p<0.001) on the proportion of offload times meeting the CIHI benchmark while increased ED visit volume and hospital inpatient volume had a significant negative impact (p<0.001). At both ED sites, the proportion of patients meeting the offload target ranged from 58-83% over the timeframe. There was a significant increase in the proportion of patients meeting the benchmark from the first quarter to the last quarter (69.6% vs 75.0%; 95% CI 3.45% to 7.38%, p=0.000). Specific interventions had varying degrees of impact on offload times.Conclusion: The proportion of patients meeting the benchmark offload time varied over the study timeframe but significantly increased with EDST implementation. Offload times are one of many outcomes we aim to improve with EDST and it remains an ongoing process as new interventions continue to be implemented. Once transformation is complete, future studies will focus on the impact of EDST on all ED flow metrics, and patient and provider satisfaction.